Arabité et poésie allemande : Adonis ou la nation des poètes - Perlwitz, Ronald (2007)
The poetical work of the Syrian poet Adonis tries to answer the question of identity in a rather complex way. The problem arising in his works is the following: how can you affirm your Arabic cultural identity if your whole work intends to study universality? And how can you take over the role of prophet for the entire humanity, if your poetry, at the same time, intends clearly to offer a new approach to Arabic poetical traditions? Adoni's work is settled in the middle of these contradictions, and tries not to solve them, but to explore them. To achieve this, Adonis uses the East not only geographically but also intellectually as a symbol of resistance against the way of life and the thinking of the West. Hence, poets of German romanticism and French poets become in his eyes poets of the Orient and therefore distinguished allies for his poetical theory.